Defective Single‐Walled Aluminosilicate Nanotubes: Structural Stability and Mechanical Properties. Issue 3 (12th January 2016) - Liou, Kai‐Hsin; Kang, Dun‐Yen
Abstract: Single‐walled aluminosilicate nanotubes (AlSiNTs) are expected to possess mechanical strength comparable to that of single‐walled carbon nanotubes (SWCNTs). Most existing theoretical studies on the mechanical properties of AlSiNTs are based on defect‐free models, despite the fact that experimental results have revealed a variety of defects in AlSiNTs. Herein we developed a method for the modeling of defective AlSiNTs to enable the quantitative investigation of relationships among defect structures, structural stability, and mechanical properties of AlSiNTs. The defect structures dealt with in the proposed models are based on experimental findings. Our assessment of the stability and mechanical strength of nanotubes is based on multiscale computational tools, including density functional theory, molecular modeling, and nanoscale continuum modeling. Our study also identified the defect structure with the most pronounced impact on the stability and mechanical properties of AlSiNTs. Abstract : Gimme a break : Defective aluminosilicate nanotubes were modeled to elucidate the relationships among defect structures, structural stability, and mechanical properties. The impact of the defect sites on the mechanical properties of aluminosilicate nanotubes was investigated.